Unsupported Copper Nanoparticles in the 1,3-Dipolar Cycloaddition of Terminal Alkynes and Azides - Alonso, Francisco (2010)
Readily prepared copper nanoparticles were found to catalyse the 1,3-dipolar cycloaddition of azides and alkynes up to rates comparable to those of microwave chemistry. Both the preparation of the nanoparticles and the click reaction are carried out under mild conditions, in short reaction times and in the absence of any stabilising additive or ligand. A variety of 1,2,3-triazoles were prepared in excellent yields. A reaction mechanism was postulated on the basis of different reactivity studies and deuteration experiments. Copper(I) acetylides were demonstrated to be the real intermediate species. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA.